Effect of aqueous or ethanol extract of coffee pulp on reproduction and biochemical constituents in rat - Tapashetti, Suresh; Narayana, K; Ramachandra, S G; Krishnamurthy, H; Honnegowda, Honnegowda (The Indian Journal of Animal Sciences, 2012)
The present study assessed the effect of oral administration of aqueous or ethanolic extract of coffee pulp 2 g/kg/day for 35, 65 or 95 days to male rats. There was no morbidity or mortality in rats given 1, 2, 4, 8 or 16 g/kg of aqueous or ethanolic extract of coffee pulp suggesting the absence of toxicity or even lethality. Compared to controls, there was no difference in the spermatogenesis, blood plasma testosterone concentration, fertility and number of pups born in the coffee pulp extract - treated male rats. The concentration of glucose, total protein, aspartate amino transferase (AST), alanine amino transferase (ALT), blood urea nitrogen (BUN), creatinine, phosphorus, calcium, sodium, potassium and haematological parameters like white blood cells (WBC), red blood cells (RBC) and haemoglobin (Hb) and body weight were similar between control and coffee pulp extract-treated rats. At the tested dose, the coffee pulp extracts did not exert any effect.